Implementation of Regional Regulation Number 13 of 2012 Concerning Waste Management in Ngawi Regency Indonesia - Vikesta Santiana Eka Saputri; Sarjiyati; Taufiq Yuli Purnama (PT. Publikasiku Academic Solution, 2026)
This study shows that the implementation of Regional Regulation of Ngawi Regency, Indonesia, Number 13 of 2012 concerning Waste Management has been carried out fairly well, although it still faces various obstacles. This study aimed to analyze the implementation of waste management policies and identify the supporting and inhibiting factors in Ngawi Regency, Indonesia. The method used was empirical legal research with a qualitative descriptive approach. Data were obtained through interviews with the Ngawi Regency Environmental Agency and literature studies consisting of laws and regulations, scientific journals, and official local government documents. Policy implementation was carried out through direct and indirect socialization, the establishment of 86 waste banks and 12 Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS3R), the provision of supporting facilities, and the strengthening of derivative regulations related to restrictions on the use of single-use plastics. Supporting factors included increased public awareness, the commitment of regional leaders, and the involvement of external partners, such as schools, micro, small, and medium enterprises (MSMEs), companies, and communities. Meanwhile, inhibiting factors included low awareness among some members of the community, budget limitations, uneven waste transportation services, and high investment costs for modern waste processing technology. This study concludes that the effectiveness of policy implementation still requires stronger resources, equitable distribution of waste services, increased institutional capacity, and sustainable community education to realize integrated and sustainable waste management.